What’s Unethical About Interprofessional Collaboration? - Lévesque, Lise (BioéthiqueOnline)

(untitled) (BioéthiqueOnline, 2015)
In this commentary, the beneficial value of the relational aspects of interprofessional collaboration is emphasized to demonstrate that conflict of interests arising in self-referrals are more complex than presented in classic cases of conflicts of interest. A dialog involving health professionals and ethicists is recommended to better understand the relational aspects that are essential to patient wellness and autonomy, in relation to the various care and organizational contexts across private and public sectors. The goal is to inform policy making on management of conflicts of interests associated with self-referrals.